Pandangan Hukum Ekonomi Islam Dalam Etika Bisnis Terhadap Kehidupan Manusia - Candra, Andi; Arista, Windi; Absi, Warmiyana Zairi; Afriani, Kinaria (Disiplin : Majalah Civitas Akademika Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2024)
This research discusses the perspective of Islamic economic law on business ethics in relation to human life. Islamic economic law, which is based on Sharia principles, offers ethical and moral guidelines in conducting business activities. Business ethics in Islam not only aim to achieve material profit but also consider aspects of justice, balance, and sustainability in social life. This research explores how the application of Islamic ethical values in business can create harmony between the interests of individuals, society, and the environment. With a literature-based qualitative approach, this article highlights the importance of integrating Islamic economic principles and modern business practices to support human well-being comprehensively. The results show that the application of Islamic business ethics can be a solution in facing global economic challenges, such as social inequality and moral crises, as well as promoting sustainable development.